2009
DOI: 10.1097/aog.0b013e3181b9d222
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Use of Laparoscopic Hysterectomy Compared With Abdominal and Vaginal Approaches

Abstract: Objective To examine factors associated with undergoing laparoscopic hysterectomy compared with abdominal hysterectomy or vaginal hysterectomy Methods This is a cross-sectional analysis of the 2005 Nationwide Inpatient Sample. All women aged_18 years or older who underwent hysterectomy for a benign condition were included. Multivariable analyses were used to examine demographic, clinical, and health system factors associated with each hysterectomy route. Results Among 518,828 hysterectomies, 14% were lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
171
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 13 publications
15
171
5
Order By: Relevance
“…Of the various surgical approaches used to remove the uterus, the majority are still approached abdominally (64%); while vaginal (22%) and laparoscopic (14%) hysterectomies continue to gain popularity 2 . However, the prevalence of hysterectomy appears to be decreasing, possibly due to the advent of less invasive therapies for management of conditions previously treated with hysterectomy 3 …”
Section: Introductionmentioning
confidence: 99%
“…Of the various surgical approaches used to remove the uterus, the majority are still approached abdominally (64%); while vaginal (22%) and laparoscopic (14%) hysterectomies continue to gain popularity 2 . However, the prevalence of hysterectomy appears to be decreasing, possibly due to the advent of less invasive therapies for management of conditions previously treated with hysterectomy 3 …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, hysterectomy has been performed abdominally through a laparotomy incision, vaginally, or laparoscopically. Over the past 25 years, technological advances, coupled with changes in practice patterns regarding route of hysterectomy, have led to an increase in minimally invasive options (1,3,4).…”
Section: Introductionmentioning
confidence: 99%
“…With over 500,000 cases performed each year, it accounts for more than $5 billion in healthcare spending (1,2). Traditionally, hysterectomy has been performed abdominally through a laparotomy incision, vaginally, or laparoscopically.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It has been reported that over two thirds of hysterectomies continue to be performed in the United States as open abdominal procedures, with the lowest rates in the Southern region. [1][2][3][4] It has been well established that minimally invasive techniques, both laparoscopic and vaginal hysterectomy, have distinct advantages over abdominal approaches, including decreased length of hospitalization, reduced postoperative infections, shorter recovery times, and decreased blood loss. [1][2][3][4][5][6][7][8][9][10][11] Historically, TVH has been the route of choice among gynecologists; training for this surgical procedure has been well integrated into Obstetrics and Gynecology residency programs over the past 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It has been well established that minimally invasive techniques, both laparoscopic and vaginal hysterectomy, have distinct advantages over abdominal approaches, including decreased length of hospitalization, reduced postoperative infections, shorter recovery times, and decreased blood loss. [1][2][3][4][5][6][7][8][9][10][11] Historically, TVH has been the route of choice among gynecologists; training for this surgical procedure has been well integrated into Obstetrics and Gynecology residency programs over the past 30 years. 5,8 The introduction of laparoscopic techniques, including Laparoscopic Assisted Vaginal Hysterectomy (LAVH), Total Laparoscopic Hysterectomy (TLH), Laparoscopic Supracervical Hysterectomy (LSH), and robotic-assisted hysterectomy (TLH/LSH), had promise to continue decreasing the numbers of AH performed in the United States; these approaches have become integrated into residency training since the early to mid-2000's.…”
Section: Introductionmentioning
confidence: 99%